A Study on Common Defect of Heritage Mosque in Kedah, Malaysia - Shahrir, Nur Anis; Mohammad Ashraf Abdul Rahman (Progress in Engineering Application and Technology, 2021)
Defect can occur at any heritage building if the building is not maintained properly. A prompt action toward defects mut be taken to avoid health and safety from being affected. This study aims to recognize the common defect of heritage and to determine the possible causes of heritage mosque defect in Kedah. This study used questionnaire as survey platform instrument. The questionnaires involved multiple choices and linear scales. The linear scales were included 5 points of ‘Very Poor’ to ‘Excellent’. The data collection then transferred into the table of percentage and frequency. The result of the study is that the common defects of heritage mosque in Kedah are crack defect, leakage defect, dampness defect, peeled paint defect, insect or termite attack defect, and spalling defect. The cause of crack defect is pressure of excessive load. Next, the cause of leakage defect is cracking of external walls. Last but not least, the cause of peeled paint is caused by excessive rain and dampness.